PENDAMPINGAN DAN PENGEMBANGAN KOMUNITAS SANTRI MILENIAL DALAM BERLITERASI DIGITAL BERBASIS SOCIAL ENTREPRENEURSHIP - Finadatul Wahidah; Dewi Sinta; Babur Rohmah; Muhammad Nasikhul Ibad (Department of Islamic Community Development, Faculty of Dakwah,Universitas Islam Ibrahimy Banyuwangi, 2022)
Advances in information technology in the era of disruption get many benefits and threats. One of the biggest threats to Indonesia is the spread of harmful content (hoax content, hate speech, bullying, radicalism, to various fraudulent practices), primarily through digital media. Poor media literacy skills will harm the information obtained related to the truth of the data. So, digital literacy skills are needed. This service is carried out in the santri community of MA Al-Qodiri Jember, using the ABCD approach. The results of community service at the Santri MA Al Qodiri Jember Community are: 1) The development of the quality of students runs optimally in implementing digital literacy; 2) The development of the quality of students runs optimally in implementing digital literacy based on social entrepreneurship; 3) The development of the quality of students runs optimally in aspects of using the environment as a source of entrepreneurship; 4) We are developing the quality of students running optimally in managing the web; 5) We are reducing hoax information at the MA Al Qodiri Jember institution. Before the assistants accompanied the institution, the sources of information already existed, and literacy was little understood.